The Influence Of School Culture And Image On The Decision Of Choosing Private High Schools In The East Jakarta Region - et. al., Irmina Pinem, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to evaluate the influence of school culture and image on the selection of high schools in East Jakarta. This research is associative quantitative research, the research was conducted using a survey method with the data analysis technique used to answer the hypothesis is the Structural Equation Modeling technique. The population in this study was 995 respondents, and a sample of 285 respondents was selected using random sampling. The research is focused on the cultural and image aspects of school selection. The results of the analysis conclude that (1) there is a direct influence of school culture on school selection, (2) there is a direct influence of school image on school selection, (3) there is a direct influence of school culture on school image.